Reduced skeletal muscle quantity and quality in patients with diabetic polyneuropathy assessed by magnetic resonance imaging. Issue 5 (5th January 2016) - Moore, Colin W.; Allen, Matti D.; Kimpinski, Kurt; Doherty, Timothy J.; Rice, Charles L.
ABSTRACT: Introduction : The aim of this study was to determine whether diabetic polyneuropathy (DPN) is associated with reduced muscle quality using MRI. Methods : MRIs of the tibialis anterior (TA) muscle were recorded from 9 individuals (5 men) with DPN (∼65 years) and 8 (4 men) age‐ and gender‐matched controls. A magnetization transfer ratio (MTR) and T2 relaxation times of the TA were calculated. Results : Despite equal voluntary activation, the DPN group was ∼37% weaker than controls, with a significantly lower proportion (∼8%) of contractile tissue and lower MTR (0.28 ± 0.03 vs. 0.32 ± 0.02 percent units). T2 relaxation time was significantly longer in the DPN group (77 ± 16 ms) compared with controls (63 ± 6 ms). Conclusions : These findings indicate a reduction in the structural integrity and myocellular protein density in the TA of those with DPN. Thus, muscle weakness in DPN is likely due to both a loss of muscle mass and a reduction in contractile quality. Muscle Nerve 53 : 726–732, 2016